INPRES NO 14 TAHUN 1967 DAN IMPLIKASINYA TERHADAP IDENTITAS MUSLIM TIONGHOA CIREBON - Popi Siti Sopiah (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2017)
AbstractAt the beginning of the Orde Baru (1966-1998), Soeharto issued a policy of assimilation to Chinese descendants in Indonesia. The aim of the policy is to make Tionghoa culture can be eliminated. The policy of the Soeharto regime was carried out through Instruksi Presiden (Inpres) No. 14 Tahun 1967. Through the policy, the Orde Baru government required all Chinese to assimilate with indigenous people through several things such as Chinese name renaming to indigenous people name, restrictions on Chinese customs movement and Chinese people must follow a religion that recognized by the government. On the basis of that, the researcher is interested to reveal more deeply related to Presidential Instruction No. 14 of 1967 and Its Implications to the Chinese Muslim Identity in Cirebon in Year 1966-1998.Keywords: Chinese Muslims, Orde Baru, Assimilation, Cirebon